An Analysis of Cultural Substitution in English to Thai Translation - Pokasamrit, Patcharee (Humanities, Arts and Social Sciences Studies, 2013)
Cultural substitution refers to the translation of some known or unknown concepts in the source language by using the substitution from the culture of the receptor language rather than by other available means of meaning equivalence. For examples, a black sheep is translated into literal Thai as a cub outside a pen rather than a person with different and unacceptable characters, and a corner stone is translated as a supreme pole, rather than an indispensable and fundamental basis. This study analyzes cultural substitution in English to Thai translation in order to document its types, linguistic patterns, and cultural significance; and to find and draw conclusions as to the translators’ opinion of this technique. In the first part of the study, culturally substituted items were randomly collected from 1000 pages of different types of English to Thai translated works which were published during B.E. 2542 (1997) to B.E. 2552 (2007). These data were then classified and listed according to their generic types and presented in categorized tables with their linguistic and cultural comments as findings. In the second part, 12 translators whose works have been published during the past 10 years were asked to fill in questionnaires and interviewed on their opinions on cultural substitute translation technique. The conclusions of the opinions are provided, and the recommendations for the use of the findings and for further research are offered.